Design and implementation of a simple and inexpensive respiratory synchronization control platform - Doyle, John (Bulletin of the National Research Centre, 2022)
Background In a number of clinical and research settings, it is desirable to have an individual breathe in a particular fixed pattern (respiratory synchronized breathing). The purpose of this brief technical report is to show how a control system for this purpose can be easily and inexpensively developed using an Arduino UNO microcontroller platform. Results We programmed an Arduino UNO microcontroller to develop a respiratory timing system with selectable respiratory rate and inspiratory to expiratory ratio. Test subjects are instructed to breathe in when the light-emitting diode (LED) is illuminated and breathe out when the LED is dark. Both the duration of inspiration and that of expiration can be easily adjusted by the user to meet various requirements. The system was tested and found to function satisfactorily. Conclusions An Arduino UNO microcontroller was used to develop a respiratory timing system. This platform is likely to be of value to clinicians and investigators looking for a simple and inexpensive system for respiratory synchronized breathing.